2010
DOI: 10.1111/j.1365-2559.2010.03509.x
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic acid nephropathy revisited: a place for innate and adaptive immunity?

Abstract: Aims:The histological features of aristolochic acid nephropathy (AAN) consist of paucicellular interstitial fibrosis, severe tubular atrophy, and almost intact glomeruli with media lesions of interlobular arteries. As an early phase of interstitial inflammation preceded peritubular fibrosis in the rat model of AAN, the aim was to investigate the presence of inflammatory cells in human AAN. Methods and results: Reports of confirmed cases and case series of AAN were reviewed in terms of interstitial inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…AA-I and AA-II, the major components of AL rhizome, were shown to possess immune-stimulatory properties [21].…”
Section: Discussionmentioning
confidence: 99%
“…AA-I and AA-II, the major components of AL rhizome, were shown to possess immune-stimulatory properties [21].…”
Section: Discussionmentioning
confidence: 99%
“…At Day 35 of the protocol, inflammatory infiltrates were still present, suggesting crucial interactions between tubular cells and immune cells. Finally, histological analyses of human AAN cases also revealed that inflammatory cells are preferentially present in the interstitium of the medullary rays and in the outer medulla even in terminal stages [135]. …”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…It was therefore concluded that vascular lesions observed in AA-intoxicated patients were not induced by AA but were more likely a late consequence of advanced kidney disease. Since then, other investigations have demonstrated a dramatic decrease in peritubular capillaries especially in the fibrotic areas in human renal biopsies as well as in experimental models [30,135,138]. In a rat model of AAN, the reduction of peritubular capillaries network was associated to a decreased expression of vascular endothelial growth factor (VEGF) and to an increased expression of HIF-1α thereby suggesting that ischemia and hypoxia are important factors contributing to AAN progression [138].…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…334 Chronic potassium deficiency has also been associated with interstitial fibrosis in both rats and humans. 341,343 An unusual form of interstitial fibrosis was reported in dogs treated with high doses of estrogens and attributed to their pharmacological effects. It is characterized by a renal interstitium widened by edema and extensive fibrosis associated with tubular damage and atrophy.…”
Section: Interstitial Fibrosismentioning
confidence: 99%